MEMPERKIRAKAN PERBANDINGAN KADAR AIR SEMEN PADA BETON KERAS - Kushartomo, Widodo; Sutandi, Arianti; Linggasari, Dewi (Universitas Tarumanagara, 2020)
Comparison of cement water content (w / c-ratio) is one important factor to determine the strength of concrete, so it is important to know the ratio of the amount of water used in a concrete mix. Many problems that arise related to the quality of concrete in ready-made buildings require an in-depth investigation of the composition of concrete materials in order to estimate the quality of concrete including the ratio of the amount of water to cement. Estimating the ratio of the amount of water to the amount of cement in hard concrete is not an easy matter, there are many factors that influence it. A number of special tests are needed on hard concrete to get the accuracy of the ratio of cement water content (w / c-ratio). A number of test specimens were prepared for testing with known water content and amount of cement. After going through the treatment process for 28 days, at the age of 60 days all test specimens are examined both chemically and volumetricly to recalculate the amount of water and cement that has been used. The calculation results show the technique used has a suitability of 99% to the planning. ABSTRAKPerbandingan kadar air semen (w/c-ratio) merupakan salah satu faktor penting untuk menentukan kekuatan beton, sehingga penting sekali mengetahui perbandingan jumlah air yang digunakan dalam suatu adukan beton. Banyak permasalahan yang muncul terkait mutu beton pada bangunan yang sudah jadi memerlukan penyelidikan yang mendalam terhadap komposisi material beton tersebut guna memperkirakan mutu beton termasuk didalamnya perbandingan jumlah air terhadap semen. Memperkirakan perbandingan jumlah air terhadap jumlah semen pada beton keras bukan merupakan suatu perkara yang mudah, ada banyak faktor yang mempengaruhinya. Diperlukan sejumlah pengujian khusus pada beton keras untuk mendapatkan akurasi nilai perbandingan kadar air semen (w/c-ratio). Sejumlah benda uji disiapkan untuk pengujian dengan kadar air dan jumlah semen yang telah diketahui. Setelah melalui proses perawatan selama 28 hari, pada umur 60 hari seluruh benda uji diperiksa baik secara kimiawi maupun secara volumetrik untuk menghitung ulang jumlah air dan semen yang telah digunakan. Hasil perhitungan menunjukkan teknik yang digunakan memiliki kesesuaian sebesar 99% terhadap perencanaan.